News for Citizens : What is this "Beveridge Report"?
1943-03 1943 1940s 2 pages MARCH, 1943 NEWS FOR CITIZENS ISSUED MONTHLY WITH THE BLUE TRIANGLE Y.W.C.A. OF GREAT BRITAIN 1. The Wage Earner — Us! 2. His Own Boss — The man with a barrow 3. The Housewife — Mostly Mothers 4. The Man of Means — Very few of them now! 5. Unwillingly to School — The Schoolboy 6. Slippered Ease — Grandfather WHAT IS THIS 'BEVERIDGE REPORT"? "GIANT WANT" (twin brother of "Giant Despair") is only a bogy-man in wartime when most of us have jobs and therefore can feed, clothe and house ourselves without overmuch financial anxiety. Or, if in the Services, the actual cash we receive is pocket-money to spend as we like. To be assured of a living is termed "social security" in Sir William Beveridge's Report,* but he adds certain additional benefits which we will outline for you. Background to the Beveridge Report To understand why the Beveridge Report is causing so much interest ("commotion" some would say) it is necessary to see it against a background of the world between two wars and the essentials of the post-war world as all thinking people are beginning to recognise them. Nearly everyone between 15 and 50 has heard of the slump of the 1920's. In general terms this meant that economic factors caused mass unemployment, and, for those in jobs, wage cuts that meant a constant tug-of-war to make ends meet. Moreover, the effects of the slump affected all our lives, for if we were not ready for a job at that time, perhaps our parents were out of work or had their pay cut drastically. In other words, the people of Britain (and of the world) were living in a state of social insecurity. To avoid another period of backsliding like this the Government determined that some form of social insurance must be introduced, and in 1941 invited Sir William Beveridge, helped by a committee of experts, to plan a scheme of social insurance. (Sir William Beveridge is the well-known economist who at one time was the Director of the London School of Economics, has at different times made a special study of the problems of unemployment, and is now Master of University College, Oxford.) It is quite impossible in this short article to do more than act as a signpost to the Report, and we hope that every sort of group will discuss it in relation to their own job, locality, way of life, and so on. The Six Divisions of the Population The first point to keep in mind is that the Beveridge Plan is for everybody, rich and poor, men and women alike, and this is clearly shown in Sir William's division of the whole population into the following six divisions:— 1 includes everyone working for a wage, i.e., most of us in the Y.W.C.A. Note, too, that this class includes those receiving a monthly or quarterly pay packet, as well as those on the weekly pay-roll. 2 includes all the people otherwise " gainfully occupied "; that is to say, people who own their own businesses, such as a doctor, or a shopkeeper, or a man selling vegetables off a barrow. 3 (a new and important one) is of housewives of working age. This is the first time that the housewife, as such, has been considered as a person contributing to the community. 4 is those people who live on independent incomes, or who cannot work through disablement from any cause. (Although you may not know it, " people of independent incomes " may sometimes face Giant Want more often than those who are gainfully occupied in some way.) 5 covers those people below working age, i.e., children below the school-leaving age, wherever it may be fixed. 6 includes all old people who cannot work. Having made these divisions, Sir William has planned that each group shall be safeguarded against actual want at any period of life - from the " cradle to the grave " and that in addition we shall all be eligible for medical treatment, allowances for children after the first one, and a funeral grant. It should be noted, however, that medical benefit will be administered separately, and is, therefore, outside the scope of the Beveridge Plan. The Plan, as a whole, provides a unified system of social insurance, and when you come to study the Report in some detail it should be remembered that, where the amount of each benefit is stated, the actual figure can only be taken as approximate, because the cost of living at a given time will be a determining factor. It should also be noted that rates of contribution and benefit do not vary with the wages of the worker, as is the case in many foreign social insurance schemes. The Family is the Unit Another basic point to keep in mind when you are reading the Report is that a man and his wife are considered as a team, and, consequently, benefits are not reckoned as so much for the man — an adult — plus the same sum for his wife, another adult. No: man and wife form the basic unit of society, the beginning of a family, and so, taking disability benefit (or sickness grant) as an example, a single adult, if off work through illness, would receive 24/- a week, but if he were married, he and his wife together would receive 40/-. The main benefits under the Beveridge Plan are as follows:— Disability Benefit. Industrial Disability Pension. Unemployment Benefit. Training Benefit. Marriage Grant. Maternity Benefit. Maternity Grant. Widows' Benefit. Guardian Benefit. Children's Allowance. Retirement Pensions. Funeral Grant. National Assistance. (A very good summary of cash benefits under the Beveridge Plan, and their application to the six classes of the population, is given in Mr. G. D. H. Cole's " Beveridge Explained.") Special Benefits First let us look briefly at some of the more special benefits — funeral benefit, marriage grant, maternity benefit and maternity grant, and National Assistance. National Assistance will be provided so that no one, because of exceptional circumstances, may be in want, and will be given after a test of needs. In other words, National Assistance is the name given to the benefit to be provided so that no one can fall between two stools. Funeral benefit will be available for everyone. A marriage grant will be given to every woman on her marriage based on her contributions before marriage: we are coming round again to the custom in this country of giving a bride a dowry — a custom still in existence (Continued overleaf) *Read with this article "Beveridge Explained," by G. D. H. Cole, "The New Statesman and Nation." Obtainable from Y.W.C.A. National Offices, Central Building (4th Floor), Great Russell Street, London, W.C.1; and "Insurance for All and Everything," by Ronald Davison, Longmans, Green and Co., 43, Albert Drive, London, S.W.19 (1s. 6d.) 243/1/9/3/2